The Right Doctor for the Job: International Medical Graduates Negotiating Pathways to Employment in Australia - Harris, Anna; Guillemin, Marilys (Diversité urbaine)

(untitled) (Chaire BMO en diversité et gouvernance, 2020)
Skilled medical migrants must negotiate complex pathways to local employment in their new home countries. Accreditation and registration systems are promoted as standardized assessments of competence. To date, literature on this topic has tended to focus on organizational, political, economic and ethical issues, rather than how individuals encounter and subsequently negotiate employment pathways. We help address this gap by drawing on ethnographic interviews with migrant doctors studying and working in Australia. We find that negotiating employment pathways is a process entailing significant financial, personal, professional and emotional investment on the doctors’ behalf. We discuss the creativity and social and emotional labour entailed and the consequences of this on what it means to be a healthcare professional in the midst of increasing global worker mobility.